2023
DOI: 10.3389/fpsyg.2023.1110287
|View full text |Cite
|
Sign up to set email alerts
|

Career adapt-ability scale -short form: Validation among early career stage of Chinese university graduates

Abstract: The Career Adapt-Ability Scale (CAAS) is the favored method among researchers for measuring career adaptability. The 12-item version of CAAS-SF, which was made by Maggiori, Rossier, and Savickas based on a change to CAAS, has been slowly used by different groups in different countries and regions. As samples for the validation of the scale in this study, 571 Chinese university graduates in the early stages of their professions were chosen. Principal component analysis and confirmatory factor analysis suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…An item was removed if its loadings were less than 0.4 or the variance of the common factor was less than 0.5. [34][35][36][37] Following the EFA, we evaluated the construct validity of the scale using CFA. Studies have shown that if the sample size is too large, the chi-square statistic will have a hard time meeting the criteria.…”
Section: Discussionmentioning
confidence: 99%
“…An item was removed if its loadings were less than 0.4 or the variance of the common factor was less than 0.5. [34][35][36][37] Following the EFA, we evaluated the construct validity of the scale using CFA. Studies have shown that if the sample size is too large, the chi-square statistic will have a hard time meeting the criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should further expand the samples from different countries to further verify and extend the conclusions of this study. Third, the 12-item version of the career adaptability scale-short form has gradually been used by different groups in different countries and regions (Song et al, 2023 ). A very recent study has shown that the career adaptability scale-short form has good reliability and validity in the Chinese sample (Song et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the 12-item version of the career adaptability scale-short form has gradually been used by different groups in different countries and regions (Song et al, 2023 ). A very recent study has shown that the career adaptability scale-short form has good reliability and validity in the Chinese sample (Song et al, 2023 ). Future research should use the career adaptability scale-short form to further explore the influencing factors of career adaptability and improve the career development of college students.…”
Section: Discussionmentioning
confidence: 99%
“…The notion of CA, which is founded upon work maturity and vocational maturation, was initially proposed by Super and Knasel in 1981 (39). At present, Savickas' notion of CA enjoys broad acceptance.…”
Section: Career Adaptabilitymentioning
confidence: 99%